Analisis Penetapan Njop Objek Pbb-P2 Khusus, Jalan Tol Di Indonesia - Ginting, Jessica Amanda; Derek, Darren Shevchenko Iszecson; Kerani, Jakat; Prayogi, Cecizia Almira; Agani, Fathi Khairi (Peneliti.net, 2025)
Fiscal decentralization in Indonesia grants local governments the authority to manage local tax revenues, one of which is the Rural and Urban Land and Building Tax (PBB-P2). One important object of PBB-P2 is toll roads, which are classified as special tax objects according to the Minister of Finance Regulation No. 85 of 2024. However, the assessment of the Market Value of Taxable Objects (NJOP) for toll roads crossing various administrative regions presents significant issues, including high administrative costs and uncertainty for investors. This study aims to analyze the problems related to toll road NJOP assessments and provide recommended solutions. The method used is a qualitative approach with a literature study, analyzing regulations on toll roads and related local tax literature. The results show that centralizing NJOP assessments to provincial level as an alternative solution could simplify the tax determination process, increase administrative efficiency, and reduce assessment costs. However, this approach also has drawbacks, such as potential tax loss and the transfer of administrative burdens to provincial governments. The researcher recommends centralizing NJOP determination at the provincial level and further research on the possibility of shifting toll roads from local to central tax objects.